2020
DOI: 10.1002/pat.5177
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of UV resistance of HDPE added with hindered amine light stabilizers with different molecular structures

Abstract: UV resistance of versatile plastics has been received attention for a long time, especially of high‐density polyethylene (HDPE). It was studied systematically that hindered amine light stabilizer (HALS) with different molecular structures had an effect on the UV resistance of HDPE. The molecular weights of the two HALS were 423.7 and 2100–3000 g/mol, respectively. It was found that the low‐molecular‐weight HALS outperforms the polymeric one of HDPE matrix in UV resistances due to the different molecular struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This was due to the low temperature of the mold during injection molding (allowing for a shorter processing cycle, but unfavorable from the point of view of the crystallization of the polymer), resulting in a high cooling rate of the molten polymer, and consequently the solidification of the material in a more amorphous form [ 33 , 54 ]. During the DSC experiment, the crystallization was performed at a low rate, which gave the molecular chain sufficient time to order into the lattice [ 55 ]. As the T c was higher for the obtained composites, it reduced their degree of supercooling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was due to the low temperature of the mold during injection molding (allowing for a shorter processing cycle, but unfavorable from the point of view of the crystallization of the polymer), resulting in a high cooling rate of the molten polymer, and consequently the solidification of the material in a more amorphous form [ 33 , 54 ]. During the DSC experiment, the crystallization was performed at a low rate, which gave the molecular chain sufficient time to order into the lattice [ 55 ]. As the T c was higher for the obtained composites, it reduced their degree of supercooling.…”
Section: Resultsmentioning
confidence: 99%
“…The freed segments in the amorphous region had sufficient mobility to rearrange into a crystalline phase, increasing the degree of crystallinity during degradation. This process is known as chemicrystallisation [ 54 , 55 ]. Observed increment of the crystallinity could also be attributed to the preferential oxidation of the amorphous phase of the iPP, as well to the formation of new crystallites induced by the chain-scission reactions [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…In FTIR spectra (Figure 3A), the broad peak observed at 3392 cm −1 was assigned to the stretching vibration of N‐H bond. The new peaks in spectral region of 3100–3500 cm −1 depicted the changes in the secondary amine group, [ 23 ] while no significant change was found at the low wavelength region. Thus, the alkyl of TH‐7‐(NO·) 2 was retained.…”
Section: Resultsmentioning
confidence: 99%
“…There are three commonly used methods to improve the UV resistance of PU, including the addition of nonreactive anti-UV additives, or anti-UV nanofillers, and using bio-based antioxidant molecules as reaction raw materials. According to the mechanism of action, nonreactive anti-UV additives can be divided into free radical scavengers that can capture active radicals generated during the UV aging of polymers, and UV absorbers that can absorb UV rays. , It has been reported that adding one type of anti-UV additive alone or combining two additives can improve the anti-UV properties of PU. However, the nonreactive anti-UV additives in the PU composites are present in free form, which may migrate during long-term use, significantly affecting the stability and mechanical properties of the composites. Anti-UV nanofillers such as TiO 2 , ZnO, etc., can absorb UV energy by internal electron leap from the valence band to conduction band and convert it to other energy releases with less energy, thus playing the role of UV absorption and shielding. , However, the addition of functional fillers may damage the mechanical properties of the composites and strongly reduce the light transmittance in the visible range, resulting in opaque composites and thus limiting the application scope.…”
Section: Introductionmentioning
confidence: 99%
“…20−24 According to the mechanism of action, nonreactive anti-UV additives can be divided into free radical scavengers that can capture active radicals generated during the UV aging of polymers, and UV absorbers that can absorb UV rays. 25,26 It has been reported that adding one type of anti-UV additive alone or combining two additives can improve the anti-UV properties of PU. 27−29 However, the nonreactive anti-UV additives in the PU composites are present in free form, which may migrate during long-term use, significantly affecting the stability and mechanical properties of the composites.…”
Section: Introductionmentioning
confidence: 99%